Elogio del silencio (Estudio Agustiniano, 2021)
Some people speak badly about the silence, more because of ignorance of its existential value than for having made a serious reflection on the subject, having assumed it in its intimacy and experienced it in the daily concretion. I believe that silence, properly experienced and oriented in one's own life, constitutes one of the great forces existing in the human interior. Although it may seem contradictory, silence speaks, sometimes more than the word. The true silence leads to the greatest revelations, which can provide meaning to the being and work of people, to their longing for truth, goodness and beauty. Let us not doubt it: the deepest truth, goodness and beauty, which do not cease to make their mystery transparent, can be reflected behind the deepest silence. Let us not be afraid then of the inner recollection, for it can show us unsuspected treasures and offer them to us with the simplicity that only serenity, the peace of the spirit, provides.
Keywords: Silence; Interiority; Mistery; Mystery; Revelation